Community social work practice in an urban context : the potential of a capacity enhancement perspective - Delgado, Melvin. 4 0 16; 5 (New York : Oxford University Press, 2000)
Community social work practice based on a capacity enhancement model offers tremendous potential for unifying communities consisting of groups from very different cultural backgrounds, and in the process of doing so, make physical changes in the community. Community Social Work Practice in An Urban Context aims to teach graduate students with an emphasis on community and urban social work how to create positive community environments in marginalized urban-based communities. The use of murals, gardens, playgrounds, and sculptures,f or example provide social workers with an opportunity to identify, engage, and plan services with communities. These projects, in turn, are based upon a community's strengths and represent an effort at developing a community's capacity to help itself with assistance from professionals. -- Provided by publisher.
pt. 1. Setting the context. Setting the context for urban community social work practice -- A foundation for community capacity enhancement practice -- Framework for community capacity enhancement practice -- Guiding principles for community capacity-enhancement practice -- pt. 2. Murals, gardens, playgrounds, and sculptures. Four types of urban community-enhancement projects (murals, gardens, playgrounds, and sculptures) -- Analysis of common and unique development tasks -- pt. 3. Application of the framework to practice and lessons learned. Application of the framework to practice: assessment -- Application of the framework to practice: mapping -- Application of the framework to practice; engagement -- Application of the framework to practice: intervention -- Application of the framework to practice: evaluation -- Reflections on practice (lessons and recommendations) / Melvin Delgado.
Includes bibliographical references (p. 220-242) and indexes.
Keywords: 2 -- 0; 6; Social Service.;Sociology, Urban.;Sociology. -- 20; 20; 2